Access to credits and indebtedness: Islamic perspective - Adamu, Idris Yahaya; Abdul Rahim, Ahmad Khilmy; Hamed, Abu Bakar (Science Publications, 2016)
The purpose of this paper is to describe, from Islamic perspective, Muslims’ concern on loans and indebtedness.The paper intends to enlighten working class Muslims on the consequences of taking unnecessary loans.Due to increasing access to financial services, banks and other financial institutions are increasingly offering loans to their customers.Thus, increasing unnecessary borrowings at the expense of their future well-being.The paper concentrate on Islamic perspective of over borrowing and indebtedness. Muslims are expected to live a moderate life, free of embezzlement and misery.Therefore, are called upon to avoid unnecessary expenditure and improve savings.The study contributes to literature of borrowings, by considering loans as last alternative and by necessity.